Chilean EFL preservice teachers’ post-reading designs: approaches to language and literary learning through picturebooks - ROMERO KARLSSON, GABRIEL VICTOR JUHANI (Contextos: Estudios de Humanidades y Ciencias Sociales, 2025)
Teaching EFL through children’s literature to young learners is becoming an important teaching strategy in many parts of the world. When carefully selected and used with a clear pedagogical purpose, children’s literature—especially picturebooks—can help improve young learners’ reading comprehension and support the development of their language skills. However, for this to happen, it is necessary that EFL preservice teachers receive proper training on how to work with children’s literature and how to prepare pedagogical materials based on these texts. This article focuses on exploring the post-reading activities designed by a group of EFL preservice teachers at a statal university in Santiago, Chile. The aim is to analyze what types of reading approaches were encouraged in the post-reading activities and what kind of activity designs were developed. The findings show a variety of strategies, with the reader-response approach being the most common. This was followed by the text-based approach, which focused on comprehension and analysis, and the language approach, which aimed to support vocabulary and grammar development. While the preservice teachers were able to design activities that combine language and literary goals, the study also suggests the need to deepen their understanding of multimodal and critical engagements with literature.